Whispers in End Hopping: High-Robustness Network Covert Channel Based on End Spreading - Zhengwen Wang; Fangxiao Li; Leyi Shi (Information, 2025)
The massive use of end information in the end hopping system not only significantly improves the proactive defense capability but also reveals great potential for covert communication. However, the development of existing network covert channels is hindered by various elimination techniques and a lack of robustness guarantees. In this paper, we first present a novel network covert channel model based on end spreading (CCES) in the end hopping system. We then propose a CCES-based scheme using m-sequence in the hypothetical scenario and theoretically analyze its characteristics, including eavesdropping resistance, loss tolerance, and robust synchronization. To evaluate the performance of the CCES scheme, three evaluation metrics are adopted: non-detectability, robustness, and transmission efficiency. Experimental results show that CCES achieves a bit error rate (BER) below 5% under 30% packet loss, entropy values ranging from 0.15 to 0.82 (comparable to normal traffic), and a transmission efficiency of up to 800 bits per second. These results confirm the CCES scheme’s strong robustness and practical applicability, outperforming traditional covert channels in both reliability and stealth.